Enhanced Saccharification Yield of Alkali Pretreated Sugarcane Bagasse Utilizing Customized Cellulase Cocktail from Trichoderma harzianum and Trichoderma viride - Kumar, Ravi; Kumar, Nitin; Gupta, Ravi (International Journal of Economic Plants, 2024)
The experiment was conducted during 2023 at Bioenergy Laboratory, Department of RBEE, College of Agricultural Engineering and Technology, CCSHAU, Hisar, Haryana, India. Compositional changes in sugarcane bagasse subjected to varying concentrations of sodium hydroxide (0.3% to 1.2%), revealing significant increases in glucan content (from 37.13% to 53.81%) alongside decreases in xylan, acid-insoluble lignin, acid-soluble lignin, ash, and other extractives. These changes were validated using microscopic technique SEM, confirming the efficacy of the pretreatment process. The utilization of a customized cellulase cocktail derived from Trichoderma harzianum and Trichoderma viride holds significant promise in enhancing the saccharification from alkali-pretreated sugarcane bagasse. This study investigates the synergistic effects of cellulase enzymes produced by these fungi on the hydrolysis of lignocellulosic biomass. The enzymatic hydrolysis process is optimized by varying enzyme dosages, reaction conditions, and incubation times to maximize the release of fermentable sugars. Results indicate a substantial improvement in saccharification efficiency with the customized cellulase cocktail, highlighting its potential for sustainable biofuel production. The pretreated sugarcane bagasse, when saccharified with Trichoderma harzianum and Trichoderma viride individually, released 254.43 mg g-1 and 325.53 mg g-1 of reducing sugars, respectively, after 40 h of incubation. In contrast, the combined enzymatic cocktail achieved a substantial increase in glucose yields (345.12 mg g-1) at 40 h, showcasing the synergistic effect of the combined enzymatic activity. This research contributes to advancing bioconversion technologies for utilizing lignocellulosic biomass resources efficiently and economically, thus addressing key challenges in sustainable energy production.